Element semiquantitative concentration of sediment core D11956TC/P - Lebreiro, Susana Martin; Antón, Laura; Reguera, Isabel; Lozano, Rocio (PANGAEA, 2025)
Semiquantitative element concentrations of 8 sections of core D11956TC/P (TC stands for trigger core; P for piston core) from the Tagus Abyssal Plain were measured at a resolution of 2 mm, performed at BOSCORF, Southampton National Center, U.K., using a COX Analytical Systems Itrax X-ray Fluorescence (XRF) scanner, and the data processed with the included bAxil software. The elements considered here (Ca, Al, Si, Ti, Fe, Rb, Sr and Zr) were extracted from a series of 15 (10 kV), 17 (30 kV) and 7 (50 kV) elements. Units are in counts per second (cps). Sediment facies are identified as hemipelagites (HP) and turbidites (T). Consecutive turbidites (without Hemipelagic sediment interlayered) are identified and labeled Ti to Tiv in the type of facies.
Keywords: deep sediment cores; deep waters; hemipelagics; Iberia; turbidites